Suicidio y riesgo social en los estudiantes de tercero de bachillerato de la Unidad Educativa Riobamba, año 2023. - Guaño Andrango, Shirley Paulina (2024)
The phenomenon of suicide is a problem of interest for several areas such as politics, medicine, philosophy, even religion, and above all in the social branch when conceiving that human beings can cause any type of damage that puts their life at risk. health and reaching the level of depriving oneself of life; caused by an external environment. For many years, suicide was proposed by a popular social imagination, thinking that it is the result of strong individual problems; Later, the branch of sociology with the contribution of Durkheim poses this fact as a social component in which responsibility falls solely on society; Being the external environment that directly influences the lives of the subjects, therefore, suicide does not correspond to an individual action. Suicide is multifactorial, so social and risk factors are actively implicit in the context of suicide: these elements contribute to this fact materializing. Social factors include characteristics such as problems in family dynamics, divorce or separation, economic problems, social pressure, isolation, while risk factors are more specific characteristics such as access to substances, mental health problems (depression, anxiety, bipolar.), have a record of suicide attempts. Emilio Durkheim also eliminated conceptions and assumptions about death and suicide, naming social space as an agent that actively influences the lives of subjects. Suicide is a topic that should not be trivialized, especially in a capitalist era in which it becomes easier to internalize the discourse of individualization with social mandates that demand a strong demand for success and improvement, in a time of constant change and lack of tact and social integration. Key words: Risk factors, social factors, stigmatization, suicide attempt, taboo.